OBSERVATION ON THE DURABILITY OF FIFTEEN SPECIES OF CCA TREATED TIMBER IN THE COCHIN HARBOUR - CHERIYAN, P V; CHERIAN, C J (Fishery Technology, 2017)
Observations on the durability of fifteen species of common Indian timber treatedwith CCA at two absorption levels, for eight years are presented. CCA tteatment has improved the durability of these timber to a great extent. T. grandis, D. indicus and X. xylocarpa give maximum durability on treatment with CCA. Less durable A. kurzi, T. nudiflora and P. longifolia when treated with CCA showed results comparable to the best species.